(-x-1)(x-2)=

Simple and best practice solution for (-x-1)(x-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-x-1)(x-2)= equation:


Simplifying
(-1x + -1)(x + -2) = 0

Reorder the terms:
(-1 + -1x)(x + -2) = 0

Reorder the terms:
(-1 + -1x)(-2 + x) = 0

Multiply (-1 + -1x) * (-2 + x)
(-1(-2 + x) + -1x * (-2 + x)) = 0
((-2 * -1 + x * -1) + -1x * (-2 + x)) = 0
((2 + -1x) + -1x * (-2 + x)) = 0
(2 + -1x + (-2 * -1x + x * -1x)) = 0
(2 + -1x + (2x + -1x2)) = 0

Combine like terms: -1x + 2x = 1x
(2 + 1x + -1x2) = 0

Solving
2 + 1x + -1x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(2 + -1x)(1 + x) = 0

Subproblem 1

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2

Subproblem 2

Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1

Solution

x = {2, -1}

See similar equations:

| (9*y^2-7*y+4)+(2*y+8)+(y^2-1)= | | 16x^2-144x+99=0 | | 86-5y=456y+22 | | 5x+5y=180 | | (9y^2-7y+4)+(2y+8)+(y^2-1)= | | 69z+4=162 | | 52140ft=mi | | 3x-6+5+9y= | | 2y-5=3y | | 3b=-26 | | 7-(2a-9)+2= | | x^2-28x+196=0 | | y-14=1(x-4) | | y-12=1(x-4) | | 666666+1000000000000000000= | | y-8=1(x-5) | | y-275=-2(x-25) | | y-12=1(x-2) | | y-7=1(x-1) | | y-26=1(x-16) | | 38=7p-18 | | 9z=4z+13 | | -4y+11=75 | | 30588x=254823 | | -3-20= | | 72=-16p^2+64p+12 | | 8x+13=5x-11 | | (0.04x^2+0.2x+12)(0.04x^2+0.2x+12)=144 | | .0016x^4+0.16x^3+1x^2+4.8x+0=0 | | -5(5n+3)=5 | | 8r^3+26r^2-24r= | | 8s^2-18st-5t^2= |

Equations solver categories